Comments to the paper "in situ observations of silver-decoration evolution under hydrogen permeation: Effects of grain boundary misorientation on hydrogen flux in pure iron", the authors: M. Koyama et al. Scripta Mater 2017; 129:48–51. (November 2017) - Gavriljuk, V.G.; Teus, S.M.
Abstract: Based on fundamental difference in diffusion mechanisms of substitutional and interstitial atoms and using molecular dynamics simulation of hydrogen migration, it is shown that accelerated hydrogen flux in the polycrystalline iron, as observed in the course of cathodic charging, cannot originate from the enhanced hydrogen grain boundary diffusion. A possible role of grain boundary cracking is supposed.